Tackling macroeconomic precariousness: The role of the composite leading indicator - Puah, Chin-Hong; Tan, Wei-tTing; Shazali, Abu Mansor; Wong, Shirly Siew Ling (International Information Institute Ltd., 2016)
The present study explored the possibility of extending the leading indicator framework to establish a composite leading indicator (CLI) for the Cambodian economy. We established the CLI on the basis of a non-parametric approach originated by the National Bureau of Economic Research (NBER). We subjected a great number of macroeconomic series to empirical scrutiny and settled on two prominent leading variables that ultimately molded a remarkable CLI that effectively tracked the precarious ebb and flow of the macroeconomic environment in Cambodia. Of note is that an average lead time of 7 months manifested great potential for CLI to evolve as a pragmatic means of near-term forecasting to prefigure the fluctuating business cycle.